The Spillover Effect of SEC Comment Letters on Qualitative Corporate Disclosure: Evidence from the Risk Factor Disclosure - Brown, Stephen V.; (Shaolee) Tian, Xiaoli; Wu Tucker, Jennifer (Contemporary Accounting Research, 2018)
ABSTRACT In this study we use the recently mandated risk factor disclosure to examine the spillover effect of the Securities and Exchange Commission (SEC) review of qualitative corporate disclosure. We find that firms not receiving any comment letter (“No‐letter Firms”) modify their subsequent year's disclosures to a larger extent if the SEC has commented on the risk factor disclosure of (i) the industry leader, (ii) a close rival, or (iii) numerous industry peers. We refer to this effect as “spillover.” Further, we find that after SEC comments on the industry leader's disclosure, No‐letter Firms also provide more firm‐specific disclosures in the subsequent year. The increased disclosure specificity reduces these firms’ likelihood of receiving SEC risk disclosure comments on their new filings. Our evidence suggests an indirect effect of the SEC review of qualitative disclosure.